Effects of Cotton Seed Powder as the Seed Medium Nitrogen Source on the Morphology and Pneumocandin B0 Yield of Glarea lozoyensis - Song, Ping; Yuan, Kai; Ji, Xiao-Jun; Ren, Lu-Jing; Zhang, Sen; Wen, Jian-Ping; Huang, He (Frontiers in Microbiology, 2018)
Pneumocandin B0 is an important antifungal drug precursor produced by filamentous fungus Glarea lozoyensis. The high broth viscosity of cultures of this organism results in lower oxygen solubility and higher energy consumption for agitation and aeration, which mostly caused by the morphologies of filamentous fungi in submerged culture. In this study, the effects of different seed medium nitrogen sources on morphology and fermentation behavior of G. lozoyensis were investigated, and cotton seed powder resulted in small, compact pellets. Moreover, pneumocandin B0 yield in Erlenmeyer flasks were increased by 22.9%. Furthermore, pneumocandin B0 yield in a 50-L fermenter reached 2,100 mg/L and the dissolved oxygen maintained above 30%. Additionally, activities of phosphofructokinase (PFK), isocitrate dehydrogenase (ICDH), glucose 6-phosphate dehydrogenase (G6PDH), and malic enzyme (ME) were increased by 87.5, 50, 41.6, and 10.7%, respectively. This study demonstrates the feasibility and advantages of using cotton seed powder for controlling the fungal morphology and improving the product yield in pneumocandin fermentations.